Determination of drying kinetics and physicochemical characterization of apricot pomace in hot-air dryer - Kayran, Seda; Doymaz, Ibrahim (SPRINGER, 2017)
The effect of different air-drying temperatures on drying kinetics of apricot pomace was investigated. The apricot pomaces were dried at 40, 50, 60 and 70 A degrees C in the cabinet dryer. It is observed that drying characteristics of apricot pomace were greatly influenced by air temperature. Color values were examined for samples with dried apricot pomace at different temperatures. Ten well-known thin-layer models were used to predict drying kinetics by nonlinear analysis of regression. The Aghbashlo et al. and Midilli et al. models best fitted the experimental data for the whole range of temperatures. Effective moisture diffusivity ranged from 1.014x10(-9) to 1.859x10(-9) m(2) s(-1) and calculated using the Fick's second law. Activation energy was estimated by a modified Arrhenius-type equation and found to be 19.41 kJ mol(-1). Color analysis showed that the values of the parameters L, a, b, C and H decreased with drying temperature.
Keywords: Apricot pomace; Color; Effective moisture diffusivity; Drying; Mathematical modeling; PRUNUS-ARMENIACA-L.; BETA-CAROTENE; APPLE POMACE; MOISTURE DIFFUSIVITY; DIETARY FIBER; BY-PRODUCTS; MICROWAVE; ANTIOXIDANT; SLICES; Thermodynamics; Chemistry